Memorandum of understanding between Universiti Teknologi MARA and The University of Newcastle, Australia / Fakulti Undang-Undang - Universiti Teknologi MARA, Fakulti Undang-Undang (Universiti Teknologi MARA (UiTM), 2017)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.